Impact of testicular histopathology as a predictor of sperm retrieval and pregnancy outcome in patients with nonobstructive azoospermia: correlation with clinical and hormonal factors. (20th December 2015) - Guler, I.; Erdem, M.; Erdem, A.; Demirdağ, E.; Tunc, L.; Bozkurt, N.; Mutlu, M. F.; Oktem, M.
Summary: In this study, our objective was to evaluate the impact of testicular histopathology on the outcome of intracytoplasmic sperm injection (ICSI) cycles of patients with nonobstructive azoospermia and correlate with clinical and hormonal parameters. For this purpose, 271 patients with nonobstructive azospermia (NOA) who underwent testicular sperm extraction (TESE) for ICSI cycles were retrospectively evaluated for sperm retrieval, fertilisation, embryo cleavage, clinical pregnancy and live birth rates among different testicular histology groups. We also correlated hormonal and clinical factors with histological findings. Sperm retrieval and fertilisation rates (FR) were found to be significantly different among all testicular histological groups of NOA except for embryo cleavage, clinical pregnancy and live birth rates. Furthermore, serum follicle stimulating hormone (FSH) level was the most significant variable to predict sperm recovery on TESE. Separate analyses within each testicular histological group revealed that higher FSH was also associated with lower pregnancy rates in only maturation arrest group. In conclusion, testicular histology significantly influences sperm retrieval and FRs but not pregnancy and live birth rates in nonobstructive azoospermia. However, FSH is the best predictor of a successful TESE.